Treating prolonged grief disorder with CBT for insomnia: A replicated single-case experimental study protocol - Thomas A. de Lang; Peter J. de Jong; Marike Lancel; Jaap Lancee; Maarten C. Eisma (PLoS ONE, 2026)
The most effective treatments of prolonged grief disorder (PGD) result in clinically relevant effects in only about half of the patients and can be emotionally taxing. This points to the importance of improving currently available treatment options. One promising target for enhancing the efficacy of the treatment of PGD is insomnia. Sleep disturbances are very common in bereavement and are proposed to play a causal role in maintaining PGD symptoms. Therefore, targeting sleep problems may be an effective treatment for people with PGD and insomnia disorder. This protocol presents a study, registered in the Dutch Trial Register (NL86238.042.24) that will evaluate the effects of cognitive behavioral therapy for insomnia (CBT-I) in individuals with comorbid PGD and insomnia using a replicated single-case experimental design (R-SCED). Twenty adults meeting diagnostic criteria for both disorders will be randomized to complete baseline between 5 and 14 weeks, after which they will receive CBT-I. Weekly PGD and insomnia symptom measures will be administered throughout the baseline (5–14 weeks), intervention (7–8 weeks) and post-intervention phase (4–13 weeks). Outcomes will be examined using visual inspection, Tau-U indices, and randomization tests. Results: We expect CBT-I to reduce both insomnia and PGD symptoms. This study will form the first systematic evaluation of CBT-I for PGD. Findings may help establish a novel, less emotionally demanding treatment option for bereaved individuals.